Exploring The Sustainability Of Hybrid Working As A Workforce Model - Mooney, Diarmuid (Global journal of Business and Integral Security, 2024)
This study offers a comprehensive analysis of the implementation and sustainability of hybrid working models in workplaces, examining both pre- and postCovid contexts. Prior to the pandemic, hybrid working was largely overlooked, with only a minority of organisations offering it and often with inadequate support for employees. However, the Covid-19 crisis precipitated a significant shift, leading to widespread adoption of hybrid working arrangements. The transition to hybrid working was accompanied by challenges, including a lack of pre-pandemic support for remote work. Nonetheless, the success of remote working during the crisis demonstrated its value, with participants reporting increased productivity and cost savings. The study identifies various hybrid working models, such as fixed hybrid, workplace-first, flexible, and remote-first, but reveals a lack of clarity on their implementation within organisations. vi Key findings highlight concerns and benefits from the perspective of employees. While flexibility was appreciated, concerns regarding motivation, workspace availability, and maintaining professional connections emerged. The blurring of boundaries between work and personal life, coupled with potential disparities in opportunities for promotion, underscores the need for clear boundaries and trust between employers and employees. From managerial perspectives, challenges in maintaining work-life balance, managing remote teams, and redefining the function of physical workplaces were evident. Despite concerns, managers expressed confidence in their ability to adapt with the right strategies in place. Participants generally expressed attachment to hybrid working due to its flexibility and work-life balance benefits. However, concerns regarding organisational culture, collaboration, and communication underscored the need for ongoing adaptation and support. Overall, while hybrid working is seen as promising, its long-term success requires addressing challenges related to remote collaboration effectively. By acknowledging these complexities and implementing appropriate strategies, organisations can cultivate sustainable hybrid work environments that benefit both employees and the organisation. This study offers valuable insights for policymakers, employers, and employees navigating the evolving landscape of hybrid work.